2011
DOI: 10.1007/978-3-642-25085-9_26
|View full text |Cite
|
Sign up to set email alerts
|

A Measure for Accuracy Disparity Maps Evaluation

Abstract: The quantitative evaluation of disparity maps is based on error measures. Among the existing measures, the percentage of Bad Matched Pixels (BMP) is widely adopted. Nevertheless, the BMP does not consider the magnitude of the errors and the inherent error of stereo systems, in regard to the inverse relation between depth and disparity. Consequently, different disparity maps, with quite similar percentages of BMP, may produce 3D reconstructions of largely different qualities. In this paper, a ground-truth based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Here we are restricting our discussion to binocular vision (left and right views). As discussed in [7] differences between two images, give depth information and these differences are known as disparities. In other words shift between stereocorresponding points is termed as disparity.…”
Section: Literature Surveymentioning
confidence: 99%
“…Here we are restricting our discussion to binocular vision (left and right views). As discussed in [7] differences between two images, give depth information and these differences are known as disparities. In other words shift between stereocorresponding points is termed as disparity.…”
Section: Literature Surveymentioning
confidence: 99%
“…where z C (x) is the distance from point x C to the plane (O C , x C , y C ), containing the focal point O C , and f is the focal length. Cabezas et al [4] identified two elements that lack in the definition of metric (9). The first is that it does not take into account the a priori error made on the depth z C during the 3D reconstruction.…”
Section: Existing Assessment Metricsmentioning
confidence: 99%
“…The percentage of Bad Matched Pixels (BMP) measures the quantity of disparity estimation errors exceeding a threshold δ (equals to 1 pixel) [12]. The Sigma-Z-Error (SZE) measures the impact of estimation errors on a 3D reconstruction based on the distance between the real depth and the estimated depth, based on ground-truth disparity and estimated disparity, respectively [17]. The Mean Relative Error (MRE) is based on the ratio between the absolute difference of estimated disparity against ground-truth disparity, and ground-truth disparity [18].…”
Section: Experimental Validationmentioning
confidence: 99%